PENINGKATAN TEKNOLOGI BUDIDAYA STROBERI MELALUI APLIKASI EKOENZIM DAN PENGGUNAAN VARIETAS UNGGUL DI NAGARI BATANG BARUS KABUPATEN SOLOK - Firsta Ninda Rosadi; Jamsari Jamsari; Roza Yunita; Reni Koja; Winda Purnama Sari; Meisilva Erona S; Lily Syukriani; Sahrul Utama; Andika Ade Saputra (LPPM Universitas Andalas, 2024)
The Lubuek Kabau Sepakat farmer group is one of the farmer groups that actively cultivates strawberry plants. However, the strawberry production obtained is not optimal because of the lack of knowledge related to organic fertilizers and the source of planting material used is not clear about the origin of the variety because it is only vegetatively propagated from the previous plant. Therefore, the objectives of this service activity are 1) to educate farmer groups about ecoenzymes so that they can be used as one of the organic fertilizers to be applied to strawberry plants; 2) to provide seedlings of superior strawberry varieties so that the quantity and quality of strawberry production can increase. The activity was carried out at the Lubuk Kabau Sepakat Farmer Group, Nagari Batang Barus, Solok Regency, West Sumatra. The stages of activities carried out include: identification of partner needs and problems, preparation of programs that are in accordance with the needs / problems of partners, implementation of activities in accordance with the plans that have been made, then monitoring and evaluation. The result of this activity is that the partners' knowledge or skills related to ecoenzyme have increased so that they are able to independently produce ecoenzyme and will apply ecoenzyme to strawberry plants. A total of 150 strawberry seedlings of the premium Sweet Japanense variety have been delivered to partners so that the quantity and quality of strawberry production can increase. The results of the activity evaluation showed that 95% of the participants were very satisfied with the activities carried out by the service team. As many as 85% of participants said that this training activity was very useful in helping to reduce organic waste in the form of fruit peel residue. The relevance of themes and materials is in accordance with the needs and can be applied in everyday life.